Isu Terorisme dalam Jurusan Hubungan Internasional Perspektif Islam - Muslikhati, Siti (Jurnal Hubungan Internasional, 2012)
The fight against terrorism must depart from the settlement of the core of problems. One of the most important roots of terrorism today is the injustice and imbalance in the system of international relations which in turn fosters an attitude of double standards to the holders of international domination and hegemony, the US and its Western allies. Only with the creation of a new international order which is fair, then terrorism can be reduced, thus creating world peace.